ВЛИЯНИЕ СКОТОВОДЧЕСКОГО ХОЗЯЙСТВА НА ЗООЛАТРИЧЕСКИЕ ВЕРОВАНИЯ В АЗЕРБАЙДЖАНЕ В VI-III ТЫСЯЧЕЛЕТИИ ДО Н.Э. (Journal of Oriental Studies, 2016)
In the given article questions on changes in zoolatryideas and cults of ancient times in connection withdevelopment of cattle-breeding in Azerbaijan in the periodof eneolit and early bronze are considered.Author mainly gives consideration to the period ofdevelopment of production economies in Azerbaijan, whentotemist cults gradually lose their positions in ideologicalВест ник КазНУ. Серия востоковедения. №2(55). 2011 13ideas of that time and their place in the cults andceremonies which positively influence the development ofcattle-breeding.In the article development of zoolatry cults isdescribed using archeological and ethnographic materials.